Inventories, Input Costs, and Productivity Gains from Trade Liberalizations - Khan, Shafaat Yar (World Bank, Washington, DC, 2021)
Sourcing internationally entails additional costs due to larger per inventory holdings. When firms switch toward foreign sources, these unobserved costs increase. This paper revisits the effect of trade liberalization on firms’ productivity taking into account the inventory premium of importing and input cost heterogeneity. Through model simulations, the paper shows that in the presence of inventory holding costs, their omission in revenue-based productivity measures leads to a systematic overestimation of the elasticity of productivity to input tariffs. Controlling for the firm’s import intensity and inventory usage in the estimation of productivity corrects for the bias. The paper studies the relevance of this potential bias during India’s trade liberalization in the early 1990s. First, it documents that inventory holdings of intermediate goods increased significantly with import intensity and input tariffs. Second, it extends a standard productivity estimation procedure with a control function of the various firm-level input costs. The mismeasurement channel accounts for around 35 percent of the estimated productivity gains. Consistent with the gradual adjustment to the tariff reductions, the bias in the response of firm-level productivity is backloaded.